The Effect of Corporate Social Responsibility Disclosure and Company Size on Financial Performance in Mining Companies on the Indonesia Stock Exchange - Nur Indah Dwi NOVITA; Muhammad Iqbal BAKRY; Jurana JURANA; Muliati MULIATI; Rahayu INDRIASARI; Arung Gihna MAYAPADA (PT Keberlanjutan Strategis Indonesia, 2025)
Testing and analyzing the impact of company size and corporate social responsibility (CSR) disclosure on return on assets (ROA) in mining businesses listed on the Indonesia Stock Exchange between 2019 and 2021 was the aim of this study. Ten businesses that satisfied the requirements based on the purposive sampling method made up the research sample, out of the 54 enterprises that made up the population. After three years of observation, thirty data analyses were produced for this study. methods for analyzing data using multiple linear regression, descriptive statistics, hypothesis testing, and traditional assumption testing. The findings demonstrated that the financial performance predicted by ROA is not significantly improved by Corporate Social Responsibility (CSR) disclosure. Furthermore, there is no discernible positive impact of company size on ROA.